1997
DOI: 10.1002/hep.510260638
|View full text |Cite
|
Sign up to set email alerts
|

Histological and clinical outcome after liver transplantation for hepatitis C

Abstract: Hepatitis frequently recurs after liver transplantation for hepatitis C. However, the histological progression of disease, predictors of recurrence and disease severity, and patient survival remain uncertain. Fifty-five patients with cirrhosis caused by chronic hepatitis C underwent liver transplantation between January 1990 and December 1993. Hepatitis C genotype was determined, and liver biopsies were performed at frequent intervals posttransplantation. The median follow-up time was 40.4 months. The cumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(30 citation statements)
references
References 25 publications
1
26
0
3
Order By: Relevance
“…On the other hand, recent reports demonstrated no difference in the patients' survival between OLT for hepatitis C and those for other liver diseases. 1,4 Our findings are also consistent with these previous studies. Unfortunately, HCV RNA by polymerase chain reaction was not available in every case because of the retrospective nature of the study; however, 93% were HCV RNApositive at the end of follow-up.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…On the other hand, recent reports demonstrated no difference in the patients' survival between OLT for hepatitis C and those for other liver diseases. 1,4 Our findings are also consistent with these previous studies. Unfortunately, HCV RNA by polymerase chain reaction was not available in every case because of the retrospective nature of the study; however, 93% were HCV RNApositive at the end of follow-up.…”
Section: Discussionsupporting
confidence: 95%
“…[1][2][3] Recently published studies showed no difference in the survival between patients with hepatitis C and those receiving liver transplants for other conditions, even though a reinfection by HCV in the recipients is nearly universal. 1,4 However, in some patients HCV reinfection induces a progressive disease which may lead to graft failure or graft cirrhosis, and the need for retransplantation. [5][6][7] The reason why some patients develop recurrent hepatitis very early after transplant while others progress slowly over several months is still unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Hepatit C Virüsü, Hepacivirüsler genusunda Flaviviridae ailesinde yaklaşık 40-50 nm çapında, dışta lipid zarf taşıyan bir virüstür (3,4). HCV'nin genomu tek zincirli pozitif sens bir RNA molekülüdür.…”
Section: Introductionunclassified
“…ORF genomun büyük bir kısmını kapsamaktadır ve yaklaşık 3010 aminoasit uzunluğunda bir poliproteini kodlar. HCV genomunun her iki ucunda (5' ve 3') ise ürüne dönüşmeyen (untranslated region, 5'UTR, 3'UTR) bölgeler bulunmaktadır (3,5).…”
Section: Introductionunclassified
See 1 more Smart Citation